DETERMINATION OF RESIDUAL STRESSES IN SEMI-FINISHED AXLES FOR RAILWAY ROLLING STOCK - Bondarev, O. M.; Gorobets, V. L.; Myamlin, S. V.; Pysmennyi, E. O.; Skogarev, I. E.; Ghorobets, D. V. (Science and Transport Progress, 2010)
In the article the analysis of comparative tests on determination of remaining tensions in the semitreated axles produced according to different technologies is conducted and the conclusions re. availability and stability of the new production technology for semitreated axles are done.